THE TABLIGHI JAMAAT RESPONSE TO THE COVID-19 PANDEMIC: A LIVING HADITH PERSPECTIVE - Asroni, Ahmad (STIT Ibnu Rusyd Tanah Grogot, 2024)
This article examines the response of the Tablighi Jamaat to the COVID-19 pandemic through the lens of living hadith. This study adopts a qualitative research design to explore and analyze the response of the Tablighi Jamaat to the COVID-19 pandemic from a theological and practical perspective, grounded in the concept of living hadith. The data for this study is collected through some methods: interview, participant observation, and document analysis. There are several findings in this research. First, the Tablighi Jamaat is an Islamic movement that frequently draws on hadith as a foundational reference in its activities, seeking to implement these teachings in everyday life. The movement generally does not engage in discussions concerning the authenticity of hadith and actively avoids theological debates. Second, the diverse responses of Tablighi Jamaat members to the COVID-19 pandemic are deeply influenced by their theological beliefs. These beliefs are shaped by their interpretations and understandings of religious texts. Members interpret these texts in a literal/textual manner, particularly hadiths related to tho’un (plague or contagious diseases). Third, for some members of the Tablighi Jamaat, the hadiths concerning tho’un are perceived solely as warnings and trials from Allah, without reference to scientific perspectives, nor do they align with the implementation of public health protocols.